ANALYSIS OF FACTORS INHIBITING DEVELOPMENT IN VILLAGES WITH SMALL POPULATIONS IN REMOTE AREAS - Hadi Permana; Zainal Fatah; Eny Haryati (International Journal of Multidisciplinary Reseach, 2026)
Development in sparsely populated villages in remote areas still faces structural barriers that have not been widely studied, especially in border areas such as Nunukan Regency, North Kalimantan. This study aims to identify factors inhibiting development in sparsely populated villages, analyze the influence of population limitations on development achievements, and formulate appropriate policy recommendations. The study used a mixed approach with a sequential explanatory design. The quantitative phase involved 92 respondents from 18 villages in 7 sub-districts selected through proportionate stratified random sampling, then analyzed using descriptive statistics and multiple linear regression. The qualitative phase involved 12 purposive informants from three locus villages in Krayan, Lumbis, and Sebatik Sub-districts, analyzed using the Miles and Huberman interactive model, then integrated through connecting and joint display techniques. The regression model proved significant with an R square of 0.616. Resources had a positive and significant effect, while Population Scale Barriers had a negative and significant effect on development achievements, while Communication, Disposition, and Bureaucratic Structure had no significant effect. Qualitative findings indicate that barriers are cumulative, that apparatus disposition is good despite limited capacity, and that geographic remoteness moderates the impact of small populations, as evidenced by the high achievement rates in villages with good access despite their small populations. This study concludes that population size is not the sole explanation for development barriers. Small populations interact with resource constraints and geographic remoteness, necessitating affirmative action policies based on a geographic difficulty index and a cluster approach between villages.